The Quasi-Judicial Authority of Bawaslu in the Perspective of Das Sollen and Fiqh Siyasah - Afriyanto, Dodi; Febrian, Febrian; Rumesten, Iza (Nurani, 2025)
This study examines the quasi-judicial authority of the General Election Supervisory Agency (Bawaslu) in handling administrative violations and disputes related to the electoral process, using das sollen and fiqh siyasah as the analytical framework. Bawaslu’s authority is formally designed to reinforce legal certainty, yet its implementation still reveals significant imbalances. Evidence from practice shows inconsistencies between the normative dimension (das sollen) and the empirical reality (das sein), indicating that Bawaslu’s institutional role as a quasi-judicial body continues to leave room for suboptimal law enforcement. The research applies a normative-comparative approach with case studies in Indonesia, Mexico, Costa Rica, and the Philippines. The analysis highlights the urgency of reconstructing Indonesia’s electoral legal system, particularly Article 462 of Law No. 7 of 2017 on General Elections, so that Bawaslu’s decisions acquire executorial power. Comparative findings reveal that Costa Rica, Mexico, and the Philippines have independent and robust electoral courts whose rulings are final and binding. Viewed from the perspective of fiqh siyasah, electoral justice is not limited to legal-formal mechanisms but also encompasses substantive justice that fulfills the function of hisbah (oversight) and safeguards the constitutional rights of citizens (hifz al-huquq).